Differential epigenetic regulation of BDNF and NT-3 genes by trichostatin A and 5-aza-2′-deoxycytidine in Neuro-2a cells - Ishimaru, Naoki; Fukuchi, Mamoru; Hirai, Akina; Chiba, Yusuke; Tamura, Tomonari; Takahashi, Nami; Tabuchi, Akiko; Tsuda, Masaaki; Shiraishi, Masahiko (Biochemical and biophysical research communications, 2010)
To understand epigenetic regulation of neurotrophins in Neuro-2a mouse neuroblastoma cells, we investigated the alteration of CpG methylation of brain-derived neurotrophic factor (BDNF) promoter I and neurotrophin-3 (NT-3) promoter IB and that of histone modification in Neuro-2a cells. Bisulfite genomic sequencing showed that the CpG sites of BDNF promoter I were methylated in non-treated Neuro-2a cells and demethylated following 5-aza-2′-deoxycytidine (5-aza-dC) treatment. In contrast, methylation status of the NT-3 promoter IB did not change by 5-aza-dC treatment in Neuro-2a cells. Furthermore, we demonstrated that BDNF exon I–IX mRNA was induced by trichostatin A (TSA) treatment. However, NT-3 exon IB–II mRNA was not induced by TSA treatment. Chromatin immunoprecipitation assays showed that the levels of acetylated histones H3 and H4 on BDNF promoter I were increased by TSA. These results demonstrate that DNA methylation and/or histone modification regulate BDNF gene expression, but do not regulate NT-3 gene expression in Neuro-2a cells.